2021
DOI: 10.1177/15562646211038819
|View full text |Cite
|
Sign up to set email alerts
|

Communicating With Diverse Patients About Participating in a Biobank: A Randomized Multisite Study Comparing Electronic and Face-to-Face Informed Consent Processes

Abstract: Some individuals’ understanding of informed consent (IC) information may improve with electronic delivery, but others may benefit from face-to-face (F2F). This randomized, multisite study explores how individuals from diverse backgrounds understand electronic IC documents versus F2F, their confidence in understanding, and enrollment in research. A total of 501 patients at two U.S. biobanks with diverse populations participated. There were no overall differences between electronic and F2F understanding, but F2F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…Different methods were used across studies to assess comprehension, some of which were more robust than others in their approaches. Overall, 10 studies included established instruments to assess comprehension, and their methodological validity was thus categorized as “high” (score=+++) [ 13 - 15 , 25 , 27 , 28 , 35 , 39 , 41 , 47 ]. The instruments used included the Brief Informed Consent Evaluation Protocol [ 15 , 52 ], Digitized Informed Consent Comprehension Questionnaire [ 14 , 51 ], MacArthur Competence Assessment Tool for Clinical Research [ 25 , 28 , 54 ], Quality of Informed Consent [ 13 , 35 , 39 , 41 , 47 , 50 ], and University of California San Diego Brief Assessment of Capacity to Consent [ 25 , 27 , 28 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different methods were used across studies to assess comprehension, some of which were more robust than others in their approaches. Overall, 10 studies included established instruments to assess comprehension, and their methodological validity was thus categorized as “high” (score=+++) [ 13 - 15 , 25 , 27 , 28 , 35 , 39 , 41 , 47 ]. The instruments used included the Brief Informed Consent Evaluation Protocol [ 15 , 52 ], Digitized Informed Consent Comprehension Questionnaire [ 14 , 51 ], MacArthur Competence Assessment Tool for Clinical Research [ 25 , 28 , 54 ], Quality of Informed Consent [ 13 , 35 , 39 , 41 , 47 , 50 ], and University of California San Diego Brief Assessment of Capacity to Consent [ 25 , 27 , 28 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 60% (6/10) of the “high” validity studies reported significantly better understanding with eConsent than paper-based ICFs for at least some of the concepts assessed using established instruments, with no statistical tests in favor of the paper process [ 14 , 15 , 25 , 28 , 35 , 39 ]. The remaining 4 (40%) of the 10 studies reported no significant difference in comprehension between eConsent and a paper-based consent process [ 13 , 27 , 41 , 47 ], with 1 study reporting statistically nonsignificant better comprehension using eConsent [ 27 ]. However, confidence in understanding was significantly lower with eConsent than with paper-based ICFs in 1 study that observed no difference in overall understanding [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For an electronic consent form to be useful and equitable, the information it provides needs to be readable, accurate, and complete . Despite national recommendations that they be written for a sixth-grade reading level, studies have shown that informed consent documents are overly complex .…”
Section: Introductionmentioning
confidence: 99%
“…13 For an electronic consent form to be useful and equitable, the information it provides needs to be readable, accurate, and complete. 14 Despite national recommendations that they be written for a sixth-grade reading level, studies have shown that informed consent documents are overly complex. [15][16][17][18][19][20][21] A possible solution to this problem is to leverage artificial intelligence, including generative large language model (LLM)−based chatbots that have been trained to respond to human-generated inquiries.…”
Section: Introductionmentioning
confidence: 99%